Cellulosic biofuel crops alter evapotranspiration and drainage fluxes: Direct quantification using automated equilibrium tension lysimeters. Issue 3 (28th January 2019) - Parish, Autumn L.; Kendall, Anthony D.; Thompson, Anita M.; Stenjem, Ryan S.; Hyndman, David W.
Abstract: An increasing number of crops are being considered as potential sources of biomass for both conventional (e.g., maize/corn) and cellulosic (e.g., switchgrass, miscanthus, and hybrid poplar) biofuels. Studies investigating the hydrologic characteristics of these crops are often conducted at either the field scale with a focus on evapotranspiration (ET) or at the plot scale where experiments generally rely on soil water storage dynamics and residual water balances. While this has led to many important insights into crop–soil water interactions under these crops, there does not appear to be any multiyear direct comparisons of the drainage fluxes under this range of biofuel crops. Furthermore, important advancements in drainage flux measurement technologies have yet to be applied to quantify hydrologic fluxes below a range of biofuel crops. Here, we use soil water content (SWC) probes and automated equilibrium tension lysimeters (AETL) to characterize detailed differences in soil water storage and drainage fluxes under conventional and cellulosic biofuel crops. The results of this study suggest that there are significant differences between subsurface water fluxes under some conventional and cellulosic biofuel crops, such as 75% greater average annual drainage and more rapid drainage accumulation under switchgrass relative to maize. Abstract : An increasing number of crops are being considered as potential sources of biomass for conventional (e.g., maize/corn) and cellulosic (e.g., switchgrass, miscanthus, and hybrid poplar) biofuels. This study uses soil water content probes and automated equilibrium tension lysimeters to characterize detailed differences in soil water storage and drainage fluxes under conventional and cellulosic biofuel crops. The results of this study suggest that there are significant differences between subsurface water fluxes under these biofuel crops, such as 75% greater average annual drainage and more rapid drainage accumulation under switchgrass relative to maize.